Novas perspectivas no Tratamento do Herpes Simples - Santos, Omar Lupi da Rosa (1995)
ln the developed countries the increasing seroprevalence of herpes simplex vims (HSV) is very relevant, particularly because the large proportion of asymptomatic infected individuals. For patients who are symptomatic there is considerable individual variation in the pattern and severity of recurrences. Selective antivirai agents have plàyed a crucial role in the treatment of this disease. Acyclovir has been shown to be effective for the treatmenr of individual ep1sodes as well as a long-term supressive therapy. New acyclovir analogues líke velaciclovir and famciclovir have an improved oral bioavailability and a better activity against the less sensitive viruses. We analise some types of treatment of herpes simplex, particularly tbe purine analogues and vaccines against HSV.